As pesquisas sobre avaliação e educação matemática apresentadas nos seminários internacionais de educação matemática (SIPEM, 2015 – 2018) - Silva, Marçal Inácio da (2020)
In this article we aim to emphasize the importance of evaluation as a fundamental role in student learning in the teaching of mathematics. Thus, we present an investigation based on the State of the Art that we have outlined on the themes of research and debates developed about evaluation in the school context. Thus, during the development of the work, a bibliographic survey was carried out, analytical readings of texts by different authors, thus qualifying our work as a bibliographic study. Evidence perceptions about some evaluative aspects of graduating and graduating students in Mathematics courses and the like, in the face of the evaluation process discussed in the works published in the annals of the GT8 of VI SIPEM 2015 and VII SIPEM 2018. Thus, SBEM was our target, a since it acts as a center for debates on production in the area of mathematics and promotes the development of critical analyzes of this production. The main objective of this work is to provide subsidies that allow significant debates on the question of mathematical assessment that lead teachers to reflect on how to assess and how to use it to help students overcome their difficulties in this discipline. Through research and studies, it is possible to change the way of evaluating, as it is not only through tests and tests that we can “measure” knowledge.